Enhancing Agricultural Industry's Performance Through Web-Based Inventory Accounting Information System Development - Firmandani, Wahyu; Eriani, Izmi Dwira; Putri, Tesa Eranti; Sauri, Sofyan; Puspitasari, Leny (Jurnal Dinamika Sosial Ekonomi, 2024)
Perumda Perkebunan Kahyangan, which is one of the industries in the plantation sector, is experiencing difficulties in managing plantation commodity inventory, this is because recording is still done manually. The research aims to develop a webbased inventory accounting information system called SIMEDi which is in accordance with the needs of Perumda Perkebunan Kahyangan. The method used in this research is a case study faced by Perumda Perkebunan Kahyangan regarding inventory management which is still done manually, which has an impact on company performance. Meanwhile, the method used to develop web-based SIMEDi applications is the agile method, which allows the development process to be carried out simultaneously to produce quality applications that suit user needs through the stages of planning, analysis, design, implementation, testing, deploy and maintenance. This research produces a SIMEDi inventory accounting information system that has functions and features that accommodate adequate inventory management for companies including plantation and warehouse stock initiation transactions, harvest, internal procurement, external procurement, production, sales, plantation and warehouse stock adjustments and price input. acquisition. This application also helps top management not only know the amount of inventory held at each plantation and warehouse location, but also the profits and costs of each inventory sold. The SIMEDi application provides data and information support that is precise, accurate and can be accessed in real time via the website, so that companies are able to meet market needs well.